2017
DOI: 10.1073/pnas.1615280114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acute lethal pulmonary inflammation by the IDO–AhR pathway

Abstract: The lung is a prototypic organ that was evolved to reduce immunopathology during the immune response to potentially hazardous endogenous and exogenous antigens. In this study, we show that donor CD4+ T cells transiently induced expression of indoleamine 2,3-dioxygenase (IDO) in lung parenchyma in an IFN-γ-dependent manner early after allogeneic hematopoietic stem cell transplantation (HSCT). Abrogation of host IDO expression by deletion of the IDO gene or the IFN-γ gene in donor T cells or by FK506 treatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 50 publications
5
51
0
Order By: Relevance
“…AhR plays a key role of tryptophan metabolism. Since the 1980s, several studies reported a role of tryptophan metabolites in the lung, including in cancer (59) and chronic inflammatory lung diseases affecting the parenchyma, such as sarcoidosis and idiopathic fibrosis (1,60). The indole/tryptamine pathway could induce the production of several indole from tryptophan that may activate AhR.…”
Section: Discussionmentioning
confidence: 99%
“…AhR plays a key role of tryptophan metabolism. Since the 1980s, several studies reported a role of tryptophan metabolites in the lung, including in cancer (59) and chronic inflammatory lung diseases affecting the parenchyma, such as sarcoidosis and idiopathic fibrosis (1,60). The indole/tryptamine pathway could induce the production of several indole from tryptophan that may activate AhR.…”
Section: Discussionmentioning
confidence: 99%
“…11,20 It has been reported that IDO may perform a pathogenic role in the progression of the inflammatory diseases. [21][22][23] IDO can change the function of Downloaded from iovs.arvojournals.org on 11/02/2020 FIGURE 5. Effects of IDO on the polarization of mouse peritoneal primary macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the depletion of tryptophan is the consequence of both the LPS-induced increase in indoleamine-2,3-dioxygenase (IDO), leading to the formation of kynurenine metabolites, as described in human pulmonary macrophages [56] and to the increase in tryptophan hydroxylase (TPH) activity, also occurring in macrophages in inflammatory conditions [57]. The effectors of the kynurenine pathway, expressed in epithelial cells and alveolar macrophages, were previously shown to be critical regulators of acute pulmonary inflammation in a murine model of lung transplantation [58]. In infectious disease models, IDO expression is increased by respiratory syncytial virus in human monocyte-derived dendritic cells and by IFN-γ and HIV in human monocyte-derived macrophages [59,60] and quinolinate is increased by HIV in monocyte-derived macrophages [49].…”
Section: Discussionmentioning
confidence: 99%